Diversity and utilization of bamboo species in Tigawasa Village, Bali - IDA BAGUS KETUT ARINASA (Society for Indonesian Biodiversity, 2005)
Tigawasa is one of the famous traditional villages as a center of bamboo handicraft in Buleleng regency-Bali. As a center of bamboo handicraft its have been wrestled since centuries. Their peoples have done traditionally bamboo conservation surrounding their house and garden too. The marginal area, river flow area and stiff slope that are outskirts of village become to focus of bamboo conservation by their peoples, too. This research conducted at Tigawasa village in June 2003 by stripe and interview methods. Two kilometers stripe length by 50 meters width; follow the direction north south of the river was investigated. To know the utilization of kind of bamboo and their product conducted by interview to craftsman and community figure. The result of inventory knew about four genus consist of 19 species planted in this village. To know those bamboo species will be presented their key of determination. The genus of Gigantochloa and Schizostachyum to dominate of their species, and have many uses of itâ€™s, also. Not less than 54 kind of bamboos handicraft product was produced in this village. The diversity of bamboos handicraft product, develop according progress of the technology and demand of period. Many of new products composed and use of color or paint develop to produce varieties of fixed product. Two-kind of product that is traditional boxes (â€œsokasiâ€) handicraft and woven bamboo (â€œbedegâ€) to become this village famous at Bali, even though in foreign countries Energetic development of bamboos home industry to come to decrease stock of raw materials. About two trucks supply from east Java regularly to anticipation of decrease local stock of raw materials every week.@ 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: inventory, utilization, bamboo species, Tigawasa village, Bali